(3OQGSI JGQjNjI ebGQfI Hjf GdTQjYI GdGSdGejI hGdbGfhf GdhVYjs - (3eMeO Ydj eMeO GMeO(B, (3GdHfGs ((3HjQhJ(B:s (3OGQ GdcJH GdYdejI(B,s, 2006)
(3GdCMcGe GdYGeI dYbO GdbQV aj GdTQjYI GdESdGejI hGdbGfhf,BKGQ YbO GdbQV aj GdTQjYI hGdbGfhf,GdYedjGJ GdeUQajI GdQHhjI hHOGFdgGs
(3HHdjhZQGajG(B:(3U(B.615-639s
Keywords: (3GdJTQjYs; (3GdbGfhfs; (3GdbQhV GdeUQajIs